2010
DOI: 10.1093/nar/gkq493
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of full-length genome and a single-stranded 7S DNA along the cell cycle in human mitochondria

Abstract: Mammalian mitochondria contain full-length genome and a single-stranded 7S DNA. Although the copy number of mitochondrial DNA (mtDNA) varies depending on the cell type and also in response to diverse environmental stresses, our understanding of how mtDNA and 7S DNA are maintained and regulated is limited, partly due to lack of reliable in vitro assay systems that reflect the in vivo functionality of mitochondria. Here we report an in vitro assay system to measure synthesis of both mtDNA and 7S DNA under a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…The top ( 32 P) and bottom (EtBr) gels show the radioactive signal and ethidium bromide staining, respectively. The even distribution of radioactivity in the 3 bands (here and Figure 3B) indicates that de novo replication in our model is distributed thorough the entire mtDNA, in contrast to other situations in which the 7S-fragment is preferentially replicated [33]. D. Effect of dTTP excess on mitochondrial dNTP pools.…”
Section: Resultsmentioning
confidence: 64%
“…The top ( 32 P) and bottom (EtBr) gels show the radioactive signal and ethidium bromide staining, respectively. The even distribution of radioactivity in the 3 bands (here and Figure 3B) indicates that de novo replication in our model is distributed thorough the entire mtDNA, in contrast to other situations in which the 7S-fragment is preferentially replicated [33]. D. Effect of dTTP excess on mitochondrial dNTP pools.…”
Section: Resultsmentioning
confidence: 64%
“…To elucidate this point, we compared endogenous levels of mtDNA and of 7S DNA detected by real-time qPCR, as described (Antes et al, 2010) in cells with affected levels of mtDNA (treatment with low levels of H 2 O 2 , see above). We found that the variations observed in the mtDNA content after exposure to H 2 O 2 , evaluated in the 12S region, and associated with changes in mREP levels (supplementary material Fig.…”
Section: Mtrip Exposes Mtdna Initiation Of Replicationmentioning
confidence: 99%
“…The physiological role of this finding is currently not understood [45]. While mitochondrial replication is not coupled to the cell cycle, formation of the abortive mitochondrial replication product 7S was recently found to be sensitive to dNTP concentration and to increase markedly during the S-phase of the cell cycle [46]. A role of Suv3 in relation to mitochondrial replication has been speculated [10,12], but it still remains to be established.…”
Section: Discussionmentioning
confidence: 99%